The application of structure equation modeling analysis for assessment and educational research - Costa, Augusto Da (COUNS-EDU: The International Journal of Counseling and Education, 2018)
The purpose of this study is discovering and confirmingthe essentialfunction of Structure Equation Modeling (SEM) Analysis for assessment and educational research. The literatures in regards to SEM analysis as method of assessment and educational research will be descriptive analyzed and explored in the light of meta-analysis. The result of the study shown that by using SEM analysis ones get empirical data and clear picture of student’s need and do right assessment and research in education. The empirical data enable scholars and government to set new or revise current education program for the future. Therefore this result should be considered as important data for government, especially Education department to establish curriculum and planning strategy of teaching and learning which is conjunction with reality in the field. It means the education program that been established and will develop really match with real life and needs of student, society and the nation. So SEM analysis is important method for each researchers and scholars to run assessment and educational research now and beyond.